Church-Based Social Relationships and Change in Self-Esteem Over Time (2009)
This study had two goals. The first goal was to see if church-based social relationships are associated with change in self-esteem. Emotional support from fellow church members and having a close personal relationship with God served as measures of church-based social ties. The second goal was to see whether emotional support from fellow church members is more strongly associated with self-esteem than emotional support from secular social network members. The data came from an ongoing nationwide survey of older adults. The findings revealed that having a close personal relationship with God is associated with a stronger sense of self-esteem at the baseline and follow-up interviews. In contrast, emotional support from fellow church members was not associated with self-esteem at either point in time. However, emotional support from secular social network members was related to self-esteem at the baseline but not the follow-up interview.